Relationship Between Sleep Hygiene And Sleep Quality in Adolescents Aged 12-15 Years (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2019)
Background: Good sleep is necessary for adolescents to maintain optimum health and cognitive function. Adolescents have a unique sleep behavior owing to the several hormonal changes they undergo and the variations in the circadian rhythms that regulate the sleep-wake cycle. One method for treating sleep problems in adolescents is ensuring sleep hygiene. We aimed to determine the relationship between sleep hygiene and sleep quality in adolescents aged 12–15 years at Junior High School 1 Indralaya. Methods: This study used a cross-sectional design. Samples were collected from 97 adolescents using the proportionate stratified random sampling technique with questionnaires. The data were analyzed using Chi Square test. Results: There was a significant relationship between sleep hygiene and sleep quality (ρ -value < 0.05). Sleeping is crucial for adolescents to maintain their performance in several activities, including the achievement of optimal learning outcomes. A superior sleep hygiene behavior will improve sleep quality. Conclusion: Provision of health education about sleep hygiene to adolescents by health workers is important for improving the adolescents sleep quality.